Resolusi Konflik Guru Pendidikan Agama Kristen (PAK) dalam Menciptakan Iklim Belajar yang Kondusif - Ali, Umar; Saingo, Yakobus Adi; Kasse, Simon; Hayer, Alfaris Max (Asatiza: Jurnal Pendidikan, 2023)
The purpose of this study was to determine the conflict resolution of PAK teachers in creating a conducive learning climate. This study uses a qualitative method. Data collection through Focus Group Discussion activities by interviewing 5 PAK teachers and 5 students in class XI SMK Negeri 2 Soe. The data were analyzed using a descriptive approach which discussed the results of the study that conflict resolution for PAK teachers had an impact on creating a conducive learning climate quite well and significantly, which was reinforced by almost all indicators of conflict resolution for PAK teachers that had been implemented optimally, such as giving a chance, discussing problems, compromising, forgiving each other, there is an agreement to maintain order. The implications can be measured from the learning climate indicators, namely the creation of a learning atmosphere away from noise in the classroom, students respect each other, students are not worried about asking questions, students do not go in and out during learning, although sometimes there is still a lack of neatness. However, in general PAK teachers have been able to optimally apply conflict resolution in creating a conducive and comfortable learning climate for students.